Respuesta :
AB1
(a) [tex]g[/tex] is continuous at [tex]x=3[/tex] if the two-sided limit exists. By definition of [tex]g[/tex], we have [tex]g(3)=f(3^2-5)=f(4)[/tex]. We need to have [tex]f(4)=1[/tex], since continuity means
[tex]\displaystyle\lim_{x\to3^-}g(x)=\lim_{x\to3}f(x^2-5)=f(4)[/tex]
[tex]\displaystyle\lim_{x\to3^+}g(x)=\lim_{x\to3}5-2x=-1[/tex]
By the fundamental theorem of calculus (FTC), we have
[tex]f(6)=f(4)+\displaystyle\int_4^6f'(x)\,\mathrm dx[/tex]
We know [tex]f(6)=-4[/tex], and the graph tells us the *signed* area under the curve from 4 to 6 is -3. So we have
[tex]-4=f(4)-3\implies f(4)=-1[/tex]
and hence [tex]g[/tex] is continuous at [tex]x=3[/tex].
(b) Judging by the graph of [tex]f'[/tex], we know [tex]f[/tex] has local extrema when [tex]x=0,4,6[/tex]. In particular, there is a local maximum when [tex]x=4[/tex], and from part (a) we know [tex]f(4)=-1[/tex].
For [tex]x>6[/tex], we see that [tex]f'\ge0[/tex], meaning [tex]f[/tex] is strictly non-decreasing on (6, 10). By the FTC, we find
[tex]f(10)=f(6)+\displaystyle\int_6^{10}f'(x)\,\mathrm dx=7[/tex]
which is larger than -1, so [tex]f[/tex] attains an absolute maximum at the point (10, 7).
(c) Directly substituting [tex]x=3[/tex] into [tex]k(x)[/tex] yields
[tex]k(3)=\dfrac{\displaystyle3\int_4^9f'(t)\,\mathrm dt-12}{3e^{2f(3)+5}-3}[/tex]
From the graph of [tex]f'[/tex], we know the value of the integral is -3 + 7 = 4, so the numerator reduces to 0. In order to apply L'Hopital's rule, we need to have the denominator also reduce to 0. This happens if
[tex]3e^{2f(3)+5}-3=0\implies e^{2f(3)+5}=1\implies 2f(3)+5=\ln1=0\implies f(3)=-\dfrac52[/tex]
Next, applying L'Hopital's rule to the limit gives
[tex]\displaystyle\lim_{x\to3}k(x)=\lim_{x\to3}\frac{9f'(3x)-4}{6f'(x)e^{2f(x)+5}-1}=\frac{9f'(9)-4}{6f'(3)e^{2f(3)+5}-1}=-\dfrac4{21e^{2f(3)+5}-1}[/tex]
which follows from the fact that [tex]f'(9)=0[/tex] and [tex]f'(3)=3.5[/tex].
Then using the value of [tex]f(3)[/tex] we found earlier, we end up with
[tex]\displaystyle\lim_{x\to3}k(x)=-\dfrac4{20}=-\dfrac15[/tex]
(d) Differentiate both sides of the given differential equation to get
[tex]\dfrac{\mathrm d^2y}{\mathrm dx^2}=2f''(2x)(3y-1)+f'(2x)\left(3\dfrac{\mathrm dy}{\mathrm dx}\right)=[2f''(2x)+3f'(2x)^2](3y-1)[/tex]
The concavity of the graph of [tex]y=h(x)[/tex] at the point (1, 2) is determined by the sign of the second derivative. For [tex]y>\frac13[/tex], we have [tex]3y-1>0[/tex], so the sign is entirely determined by [tex]2f''(2x)+3f'(2x)^2[/tex].
When [tex]x=1[/tex], this is equal to
[tex]2f''(2)+3f'(2)^2[/tex]
We know [tex]f''(2)=0[/tex], since [tex]f'[/tex] has a horizontal tangent at [tex]x=2[/tex], and from the graph of [tex]f'[/tex] we also know [tex]f'(2)=5[/tex]. So we find [tex]h''(1)=75>0[/tex], which means [tex]h[/tex] is concave upward at the point (1, 2).
(e) [tex]h[/tex] is increasing when [tex]h'>0[/tex]. The sign of [tex]h'[/tex] is determined by [tex]f'(2x)[/tex]. We're interested in the interval [tex]-1<x<5[/tex], and the behavior of [tex]h[/tex] on this interval depends on the behavior of [tex]f'[/tex] on [tex]-2<x<10[/tex].
From the graph, we know [tex]f'>0[/tex] on (0, 4), (6, 9), and (9, 10). This means [tex]h'>0[/tex] on (0, 2), (3, 4.5), and (4.5, 5).
(f) Separating variables yields
[tex]\dfrac{\mathrm dy}{3y-1}=f'(2x)\,\mathrm dx[/tex]
Integrating both sides gives
[tex]\dfrac13\ln|3y-1|=\dfrac12f(2x)+C\implies\ln|3y-1|=\dfrac32f(2x)+C[/tex]